ĐA DẠNG THÀNH PHẦN LOÀI CHIM KHU VỰC QUẦN ĐẢO TRƯỜNG SA, TỈNH KHÁNH HÒA, VIỆT NAM - Phạm, Hồng Phương; Lê, Xuân Đắc; Đinh, Thê Dũng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
DIVERSITY OF BIRD SPECIES COMPOSITION IN TRUONG SA ISLANDS, KHANH HOA PROVINCE, VIETNAMTwo bird surveys were conducted in Truong Sa Islands (Spratly Islands), Khanh Hoa province, Viet Nam (from October 13 to November 21, 2020 and May 16 to June 21, 2021). A total of 110 bird species belonging to 34 families and 13 orders had been recorded. One of them is listed in the IUCN Red List as Near-threatened as: Grey-tailed Tattle. One of them is listed in the Vietnam Red Data Book as Endangered as Great cormorant. Among recorded species, the most abundant are Passeriformes (45 species accounting for 40.9%), next are Charadriiformes (25 species - 22.7%), Pelecaniformes (12 species - 10.9%), Cuculiformes and the Accipitriformes (6 species - 5.5%). The surveys were also recorded the first time Chestnut cheeked starling - Agropsar philippensis (Forster, 1781) in Vietnam.